Skin, Veins and Legs - Neumann, H.A.M. (Phlebologie, 2011)
Skin, veins and legs are the three ingredients which compose together the symptom complex know as chronic venous insufficiency (CVI). High ambulatory venous pressure is transferred by simple physical laws to the skin microcirculation. The capillaries are not resistant to this high pressure and will leak water, erythrocytes and plasma proteins into the in-terstitium. The result is oedema, pigmentation, sclerosis, inflammation and ulceration. Although many forms of intervention for incompetent veins are available, compression therapy is still the cornerstone in the treatment of CVI. Beside the interface pressure, the stiffness of the compression material is essential. By increasing the stiffness the difference in pressure during walking increases and with this the massage effect of the therapy.Thermo-ablation is the treatment for varicose veins today. Knowledge about the development and transfer of the intravascular heat is essential to understand this treatment. New experiments, specially about steam development from the heat source in the blood are of great importance for the success rate. Fine tuning in those physical parameters is needed to optimally this treatment.
Keywords: Chronic venous insufficiency; Microcirculation; Skin alterations